Analisis Ketimpangan Pendapatan dan Faktor-Faktor yang Mempengaruhinya di Kabupaten/Kota Provinsi Jambi - Emy Haryaty Nengsih; Syamsurijal Tan; Erni Achmad (J-MAS (Jurnal Manajemen dan Sains), 2023)
The aims of this research are 1). To find out and analyze income inequality in the Regency/City of Jambi Province in the 2013-2021 period. 2). To find out and analyze what factors influence district/city income inequality in Jambi Province in the 2013-2021 period. The method used in this research is panel data (time series and cross section) in 11 regencies/cities of Jambi Province in 2013–2021. The model chosen in this study is the REM model (random effect model). The results obtained were that the TPT and HDI variables had a positive and significant effect on district/city income inequality in Jambi Province in 2013-2021. Meanwhile, the variable Economic Growth has a positive and insignificant effect on district/city income inequality in Jambi Province in 2013-2021, while TPAK has a negative and insignificant effect on district/city income inequality in Jambi Province in 2013-2021.